KAJIAN BIAYA PENGGANTIAN INVESTASI PEMANFAATAN LAHAN HUTAN DALAM RANGKA PENGELOLAAN SAMPAH RAMAH LINGKUNGAN: Studi Kasus Nambo - Setiasih Irawanti; Ismatul Hakim; Dian Charity Hidayat; Dewi Ratna Kurniasari; Jonny Holbert (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2017)
The high dependence of the community on forest resources led the state forest areas in Java managed by Perhutani to apply Community Based Forest Management approach (Pengelolaan Hutan Bersama Masyarakat)programme. In this programme, forest farmers become the member of Forest Village Community Institution (Lembaga Masyarakat Desa Hutan) to carry out upland rice and maize intercropping. Production forest area inthe village of Nambo and Lulut are categorized as the class of pine bussines that produce gondorukem, turpentine, and timber, as well as upland rice and maize from intercropping. Utilization of 40 ha forest area for the processing and final waste area (TPPAS) in Nambo area for 35 years must be required to pay replacement cost of investment due to the opportunity loss to invest in pine plantations and intercropping businesses. The replacement cost is calculated by using the loss opportunity of interest (LOI) method. The resuts are shown that the replacement cost for pine plant investment of Perhutani amounted to Rp5,492,318,000 and the replacement cost for upland rice and corn crops investment of LMDH members amounted to Rp798,947,520.